LncRNA TM4SF19-AS1 exacerbates cell proliferation, migration, invasion, and EMT in head and neck squamous cell carcinoma via enhancing LAMC1 expression - Zhi Yu; Xin Wang; Kai Niu; Le Sun; Dongjie Li (Cancer Biology & Therapy, 2022)
Head and neck squamous cell carcinoma (HNSCC) is a heterogeneous and aggressive tumor with high mortality and unfavorable prognosis. Numerous long non-coding RNAs (lncRNAs) have been confirmed to exert pivotal parts in cancers. Nevertheless, the functions of most lncRNAs in HNSCC need deeper exploration. Our present research tried to clarify the biological role of TM4SF19 antisense RNA 1 (TM4SF19-AS1) and investigate its regulatory mechanism in HNSCC. RT-qPCR analysis was done to test TM4SF19-AS1 expression and identify the up-regulation of TM4SF19-AS1 in HNSCC cells. Loss-of-function assays were also involved, and the data implied that TM4SF19-AS1 knockdown hampered the proliferation, migration, invasion, along with epithelial-mesenchymal transition (EMT) of HNSCC cells. In vivo assays revealed TM4SF19-AS1 depletion restrained HNSCC tumor growth. Additionally, mechanism experiments were implemented to uncover the underlying regulatory mechanism of TM4SF19-AS1 in HNSCC cells. It turned out that TM4SF19-AS1 modulated laminin subunit gamma 1 (LAMC1) expression via sequestering microRNA-153-3p (miR-153-3p) and recruiting heterogeneous nuclear ribonucleoprotein C (HNRNPC) protein. Rescue assays confirmed that TM4SF19-AS1 contributed to HNSCC cell malignant behaviors via up-regulating LAMC1. To summarize, TM4SF19-AS1 played an oncogenic role in HNSCC cells, signifying TM4SF19-AS1 may have the potential to be used as a novel molecular target for HNSCC diagnosis.